Root Morphology of Eight Hybrid Oil Palms Under Iron (Fe) Toxicity - Aprilia Ike Nurmalasari; Eka Tarwaca Susila Putra; Prapto Yudono (Jurnal Ilmu Pertanian, 2016)
The research aims to study the change of morphology root characters of eight hybrid oil palms under iron toxicity (Fe). Field experiment done in arranged in a Randomized Complete Block Design (RCBD) two factors and three blocks as replications. The first factor was Fe concentration. It consists of two levels which are concentration 0µ.g-1 and concentration 600 µg.g-1 Fe. The second factor is the hybrid of oil palms which consists of eight hybrid oil palms as Yangambi, Avros, Langkat, PPKS 239, Simalungun, PPKS 718, PPKS 540 and Dumpy. Fe was applied by pouring FeSO4 solvent for 600 µg.g-1 500 ml.-1plant.-1day-1 on two months of plants after transplanting in the main nursery. Data were collected on root morphology and plant dry weight The data were analysis of variance (ANOVA) at 5% significanly, followed by Duncan's multiple range test (DMRT). The relationships by among variables were determined by correlation analysis. The results showed that Fe concentration 600 µg.g-1 inhibits relatively root growth rate, narrows surface area, reduces the diameter, and shrinks root volume of all hybrid oil palms tested. The slowing relatively root growth rate, narrowing of root surface area and root diameter also root volume shrinkage due to Fe stress. It was also shown that the dry weight of plants was inhibit by existing of Fe toxicity.